CONTEXT AND STUDENTS' UNDERSTANDING ON PHRASAL VERBS : A Quasi-Experimental Study in One State Vocational School in Tasikmalaya - Novianti, Wiena (2015)
This study aims to measure the effect of context on students' understanding on phrasal verbs. This study also aims to investigate the students' attitudes toward the implementation of the teaching phrasal verbs through context. This quantitative study involved two classes of second-grade-mining geology students at one vocational high school in Tasikmalaya. The data for this study were obtained from two resources that were tests and questionnaires. The data from pre- and post-tests were analyzed by using Mann Whitney U test as a non- parametric statistics, since the data were not distributed normally (Larson-Hall, 2010:376). On the other hand, the data from questionnaires were analyzed by using descriptive statistics (Gaur &Sanjaya, 2009: 38). The results of the study show that context had positive effect on students' understanding on phrasal verbs. The effectiveness could be seen from the comparison of the mean rank scores of the post-test scores of the two classes. It was 25.67 for the control class and 34.18 for the experimental class. The Mann Whitney U test determined the effectiveness in which the P value (0.049) was less than the critical alpha (0.050). This means the alternative hypothesis was accepted and the null hypothesis was rejected. The results also show that students had positive attitudes (affective, cognitive, behavior) toward the implementation of the teaching method. In conclusion, the students' attitudes toward the implementation of teaching phrasal verbs through context were consistent with the results of the experiment. Perhaps, it was the combination of the nature of the method and the students' positive attitudes that determined the progressin the experimental class. To conclude, pedagogically, the results may encourage the teacher to make use the context in helping the students understand phrasal verbs. Theoretically, the result of the study may contribute to the enrichment of the theories about teaching phrasal verbs through context. Moreover, it might give an insight for further or similar research in the future. Penelitianinibertujuanuntukmelihatseberapabesarpengaruhkonteksterhadappemahamansiswamengenai 'phrasal verbs'.Penelitianinijugabertujuanuntukmenyelidikisikapsiswaterhadappelaksanaanmengajar 'phrasal verbs'melaluikonteks.Penelitiankuantitatifinimelibatkanduakelassiswageologipertambangan di salahsatu SMK di Tasikmalaya.Datauntukpenelitiandiperolehdariduasumberyaitutesdankuesioner.Data dari'pre-test'dan'post- test' dianalisisdenganmenggunakanuji Mann Whitney yang merupakanstatistiknon-parametrik, karena data tidakterdistribusinormal (Larson-Hall, 2010: 376).Sedangkan data darikuesionerdianalisisdenganmenggunakanstatistikdeskriptif(Gaur &Sanjaya, 2009:38).Hasilpenelitianmenunjukkanbahwakonteksmemilikiefekpositifpadapemahamansiswapada'phrasal verbs'.Efektivitastersebutdapatdilihatdariperbandingannilaiperingkat rata-rata dariskor post-test dariduakelas, kelaseksperimendankelaskontrol.Nilaiperingkat rata-rata 25,67untukkelaskontroldan 34,18 untukkelaseksperimen. UjiMann Whitney menentukankeefektivitasanmetodeini, dimananilai P (0.049) lebihkecildarinilaikritikal alpha (0.050).Iniberartihipotesisalternatifditerimadanhipotesisnolditolak. Hasilpenelitianjugamenunjukkanbahwasiswamemilikisikappositif (afektif,kognitif, perilaku) terhadappelaksanaanmetodepengajaran. Kesimpulannya, sikapsiswaterhadappelaksanaanpengajaran'phrasal verbs' melaluikontekskonsistendenganhasilpercobaan.Mungkin,halinimerupakankombinasidarimetodeitusendiridansikappositifrata-rata parasiswayang menentukankemajuan di kelaseksperimen. Sebagaikesimpulan, secarapedagogis, hasilpenelitianinidapatmendorong guru untukmenggunakankonteksdalammembantusiswamemahami'phrasal verbs'. Secarateoritis, hasilpenelitianinidapatmemberikankontribusipadateoritentangmengajar 'phrasal verbs' melaluikonteks. Selainitu, hasildaripenelitianinijugamemberikanwawasanuntukpenelitianserupaataulebihlanjut di masamendatang.